Association between polypharmacy and depression relapse in individuals with comorbid depression and type 2 diabetes: a UK electronic health record study. (March 2023) - Jeffery, Annie; Bhanu, Cini; Walters, Kate; Wong, Ian C. K.; Osborn, David; Hayes, Joseph F.
Abstract : Background: Individuals with physical comorbidities and polypharmacy may be at higher risk of depression relapse, however, they are not included in the 'high risk of relapse' group for whom longer antidepressant treatment durations are recommended. Aims: In individuals with comorbid depression and type 2 diabetes (T2DM), we aimed to investigate the association and interaction between depression relapse and (a) polypharmacy, (b) previous duration of antidepressant treatment. Method: This was a cohort study using primary care data from the UK Clinical Practice Research Datalink (CPRD) from years 2000 to 2018. We used Cox regression models with penalised B-splines to describe the association between restarting antidepressants and our two exposures. Results: We identified 48 001 individuals with comorbid depression and T2DM, who started and discontinued antidepressant treatment during follow-up. Within 1 year of antidepressant discontinuation, 35% of participants restarted treatment indicating depression relapse. As polypharmacy increased, the rate of restarting antidepressants increased until a maximum of 18 concurrent medications, where individuals were more than twice as likely to restart antidepressants (hazard ratio (HR) = 2.15, 95% CI 1.32–3.51). As the duration of previous antidepressant treatment increased, the rate of restarting antidepressants increased – individuals with a previous duration of ≥25 months were more than twice as likely to restart antidepressants than those who previously discontinued in <7 months (HR = 2.36, 95% CI 2.25–2.48). We found no interaction between polypharmacy and previous antidepressant duration. Conclusions: Polypharmacy and longer durations of previous antidepressant treatment may be associated with depression relapse following the discontinuation of antidepressant treatment.